Risk Management of Cinnamon Commodity Marketing in Mojokerto - Siska, Adela Silviana; Soedarto, Teguh; Laily, Dona Wahyuning (Universitas Muhammadiyah Pontianak, 2025)
One of Indonesia's leading commodities, characterized by high economic value and broad market demand both domestically and internationally, is cinnamon, which is frequently utilized in the food, pharmaceutical, and cosmetics industries. This research aims to deeply analyze the marketing risks experienced by distributors, thereby identifying the main opportunities and challenges in enhancing cinnamon marketing at UD Hilal Jaya Makmur, Mojokerto, by employing a descriptive qualitative and quantitative methodological approach, along with Failure Mode and Effects Analysis (FMEA), Fishbone Diagram, and Pareto analysis. The research findings indicate that the primary risks faced include uncertain price fluctuations and high transportation costs, while opportunities arise through marketing digitalization and establishing long-term contracts with partners, given the high global demand for spices. However, significant challenges persist, encompassing limited market access, inconsistent product quality standards, and continuously rising distribution costs; therefore, it is recommended that the company create stable price contracts with regular buyers, enhance the raw material storage system to maintain quality, implement quality standards compliant with regulations, expand sales reach via both offline and online channels, and overall improve distribution efficiency to address these challenges and support business sustainability.